Analisis Sistem Kepegawaian Berbasis Kompetensi di Kantor Camat Padang Barat - Ningsih, Viqy Andrian; Mensyla, Sofie Lorent; Putri, Resti Aprilia; Wibi, Shellin Maretha; Hanoselina, Yulia (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
A competency based personnel system has become one of the effective approaches to enhancing bureaucratic effectiveness and improving the quality of public services. This approach emphasizes the placement and development of employees based on the alignment between their qualifications, skills, and job requirements, thereby enabling each individual to contribute optimally to the achievement of organizational performance. This study aims to analyze the implementation of a competency based personnel system at the Padang Barat Sub-district Office, its impact on employee performance, and the strategies applied to address budget limitations. The research employed a descriptive qualitative method, with data collected through observation, semi-structured interviews, and analysis of official documents such as performance reports, organizational charts, and training records. The findings indicate that the implementation of the competency-based system is carried out through Job Analysis and Workforce Needs Analysis as the basis for assigning employees according to their qualifications and competencies. Although formal development through training programs remains limited due to budget constraints, the subdistrict leadership has optimized non-formal coaching through weekly meetings, mentoring, and the utilization of digital platforms such as e-Performance. The implementation of this system has proven to enhance discipline, responsibility, work efficiency, and the quality of public services, as reflected in faster service delivery and increased public satisfaction. Therefore, the application of a competency-based personnel system at the Padang Barat Subdistrict Office can be considered effective in improving both individual and organizational performance, and in supporting the realization of professional, adaptive, and service-oriented governance.